STUDY OF FINANCIAL TECHNOLOGY: THE INFLUENCE OF RISK PERCEPTION, FINANCIAL LITERACY, AND TRUST ON INVESTMENT DECISION - Setiadi, Niklaus Serafino; Budiyono, Elizabeth Fiesta Clara Shinta (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The rapid advancement of technology in the 21st century has significantly transformed daily life, including the development of Indonesia’s technology-based financial industry known as financial technology (Fintech). Generation Z increasingly utilizes Fintech platfor ms for investment activities. This study aims to analyze the influence of risk perception, financial literacy, and trust on investment decision-making among Generation Z in Yogyakarta. The research employed a correlational design with multiple regression analysis to examine the relationships between variables. Data wer collected through a structured questionnaire consisting of 36 items, with 240 respondents participating, exceeding the minimum required sample size. Data analysis was conducted using SPSS versi 25. The findings indicate that risk perception has a significant negative effect on investment decisions, while financial literacy positively influences informed decision-making. Trust in Fintech platforms also plays a crucial role in encouraging investment participat ion. This study importance of enhancing financial education & trust to support sustainable behavior among Generation Z in the digital era.